2018
DOI: 10.1039/c8ra06474a
|View full text |Cite
|
Sign up to set email alerts
|

Micro-supercapacitors based on oriented coordination polymer thin films for AC line-filtering

Abstract: Micro-supercapacitors exhibiting excellent AC line-filtering with oriented coordination polymer thin-film electrodes are fabricated based on a substrate-independent electrode fabrication strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…The chemical structure differences of pristine Ni‐NH and Ni‐S were identified by Fourier‐transform infrared spectroscopy (FTIR) (Figure S1, Supporting Information). Typical chemical bonds are observed from the spectra of both Ni‐NH and Ni‐S, for example, the N‐H stretching vibration at the frequency of about 3270 cm −1 , the stretching vibration of the aromatic ring from 1390 to 1470 cm −1 , and the C‐N stretching vibration at 1034 cm −1 . To be differentiated that, the strong peaks at 1034 and 846 cm −1 , which are ascribed to the C‐S bond, could only be observed from Ni‐S.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The chemical structure differences of pristine Ni‐NH and Ni‐S were identified by Fourier‐transform infrared spectroscopy (FTIR) (Figure S1, Supporting Information). Typical chemical bonds are observed from the spectra of both Ni‐NH and Ni‐S, for example, the N‐H stretching vibration at the frequency of about 3270 cm −1 , the stretching vibration of the aromatic ring from 1390 to 1470 cm −1 , and the C‐N stretching vibration at 1034 cm −1 . To be differentiated that, the strong peaks at 1034 and 846 cm −1 , which are ascribed to the C‐S bond, could only be observed from Ni‐S.…”
mentioning
confidence: 98%
“…Among them, metallically‐conductive 2D frameworks have gained considerable efforts as effective materials for field‐effect transistors, supercapacitors, and batteries . Nevertheless, their 1D alternatives, which possess similar repeating units and redox properties are keeping unexplored for electrochemical cells. Such linear conjugated coordination polymers, which are often obtained through the coordination of d 8 metal ions and conjugated tetradentate ligands, are able to provide good chemical stability due to their strong intermolecular interactions .…”
mentioning
confidence: 99%
“…For SCs based on monometallic organic compounds, cobalt is the most commonly used metal in the first transition metal series 25,27,50,67,69,72,73,97‐134 . Summarized in Tables 3 and 4 are the electrode and SC performances of cobalt‐organic compounds and their composites ( 12 ‐ 92 ).…”
Section: Monometallic Metal‐organic Compounds and Their Compositesmentioning
confidence: 99%
“…Besides Co‐MOFs with polycarbonate and imidazolate ligands, there are also reports on cobalt coordination polymers based on POMs ( 79 ‐ 81 ), 130 phthalocyanine‐derivatives ( 82‐85 , Figure 7A), 131 1,2,4,5‐benzenetetramine (BTA, Figure 9; 90 and 91 ), 133 and diisocyano ( 92 , Figure 7B) 134 ligands. Hua and coworkers reported that a facile method can be used to construct large scale and highly oriented uniform coordination polymer (Co‐BTA, 90 and 91 ) thin films 133 . The symmetric micro‐SC based on Co‐BTA showed a high C v of 23.1 F cm −3 on rigid Si substrates ( 90 ) and 22.0 F cm −3 on flexible polyethylene terephthalate substrates ( 91 ).…”
Section: Monometallic Metal‐organic Compounds and Their Compositesmentioning
confidence: 99%
“…Together with the liquid electrolytes, the gel electrolytes including hydrogels and ion‐gels were adopted for developing the quasi‐solid‐state high‐frequency SCs to follow the future trend of advanced electronic devices such as stretchable/flexible SCs or micro‐SCs (MSCs), [ 44,60,74–76 ] weavable fiber‐shaped SCs, [ 77–81 ] and on‐chip MSCs. [ 55,63–65,82 ]…”
Section: Introductionmentioning
confidence: 99%